Estimation of terrestrial heat flow in hydrothermally active areas based on long-term bedrock temperature observations: a case study of northwestern Yunnan, China - Wang, Wenchao; Liu, Qiongying; Chen, Shunyun; Liu, Peixun; Chen, Lichun (Frontiers in Earth Science, 2023)
Terrestrial heat flow plays an important role in the study of plate tectonics, geothermal resource exploration and earthquake genesis. The measurement of terrestrial heat flow usually utilizing deep boreholes, which is expensive and inconvenient for high altitude or mountainous terrain. In hydrothermal active areas, the temperature distribution would be disturbed by heat convection, resulting in difficulty in obtaining the conductive heat flow. In fact, heat can be used as a tracer to quantify groundwater ﬂow. The velocity of groundwater flow can be calculated by long-term subsurface temperature observation at multiple depths. Then, the influence of hydrothermal activity would be corrected to obtain the conductive heat flow reflecting the deep thermal background. This article presents a calculation method of terrestrial heat flow suitable for hydrothermal active areas. The method uses temperature-time series at different depths of the shallow crust to obtain the groundwater flow rate. The convective heat flux component can be removed based on information of groundwater movement, and then conductive heat flow can be acquired. This method has been applied to the estimation of terrestrial heat flow in the northwestern Yunnan, China which is a hydrothermal active area. The heat flow obtained through our method ranges from 54.5 to 130.3 mW/m2, with an average value of 94.5 mW/m2, consistent with the high-quality measured heat flow values in the boreholes. This study provides new perspectives for acquiring terrestrial heat flow in areas that is affected by fluid activities.